Computational extracting solutions for the perturbed Gerdjikov-Ivanov equation by using improved modified extended analytical approach - Samir, Islam; Badra, Niveen; Seadawy, Aly R.; Ahmed, Hamdy M.; Arnous, Ahmed H. (Journal of geometry and physics, 2022)
In this work, the improved modified extended tanh function method will be applied to study the perturbed Gerdjikov-Ivanov equation (PGI) which describe the dynamics of the soliton in optical fibers. New exact solutions for the PGI equation will be introduced including Weierstrass elliptic, Jacobi elliptic, dark and bright solitons, singular periodic and rational type solutions. Moreover, for the physical illustration of the obtained solutions, 3D and 2D graphs are presented.